2010
DOI: 10.3832/ifor0551-003
|View full text |Cite
|
Sign up to set email alerts
|

Domestic use of biomass fuel in the rural Meghna floodplain areas of Bangladesh

Abstract: © iForest -Biogeosciences and Forestry IntroductionBiomass fuels contribute to the largest share of the energy uses in Bangladesh. Currently, biomass is the fourth largest source of energy which supplies 15% of the energy use in the world (Sudha & Ravindranath 1998). Only in the developing countries, traditional biomass fuels meet a large percentage (38%) of the total energy needs (Sudha et al. 2003). In some countries like Bangladesh, its use is as so high as 75-90%, mainly used for cooking and heating (Sudha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 30 publications
8
13
1
Order By: Relevance
“…Nevertheless, this study found a significant positive relationship between household income and energy expenditure, which indicated that households with higher incomes were likely to spend more money for better energy fuels, such as firewood, LPG, and electricity. A similar type of attitude towards energy expenditure has been reported by other studies (Bhatt and Sachan 2004;Rao and Reddy 2007;Akther et al 2010). One of the important findings of this study was that there was a reciprocal relationship between family size and energy household energy consumption.…”
Section: Evaluation On the Perspectives Of Household Energy Consumptisupporting
confidence: 88%
See 2 more Smart Citations
“…Nevertheless, this study found a significant positive relationship between household income and energy expenditure, which indicated that households with higher incomes were likely to spend more money for better energy fuels, such as firewood, LPG, and electricity. A similar type of attitude towards energy expenditure has been reported by other studies (Bhatt and Sachan 2004;Rao and Reddy 2007;Akther et al 2010). One of the important findings of this study was that there was a reciprocal relationship between family size and energy household energy consumption.…”
Section: Evaluation On the Perspectives Of Household Energy Consumptisupporting
confidence: 88%
“…crop residues with firewood, whereas middle-class households chose a mixture of both types, and poor households selected inferior types of biomass fuels. Similar patterns of firewood use and selection were reported among different socio-economic groups in many parts of rural Bangladesh (Miah et al 2003;Jashimuddin et al 2006;Akther et al 2010) and in India (Mahapatra and Mitchell 1999;Pachauri 2004).…”
Section: Evaluation Of Households' Preferences Attitudes Knowledge supporting
confidence: 64%
See 1 more Smart Citation
“…Though controlled firewood collection from Sal forests is not completely destroying the forests and woodlands, its massive collection might affect the regeneration and conservation of forests. On the other hand, firewood is the most important wood product in Bangladesh, and the estimated demand and supply for the years 1993 to 2013 (by FMP) shows that firewood is almost one-third of the total demand (Akther et al 2010). The gap between demand and supply of firewood would easily explain the national crisis of firewood in Bangladesh.…”
Section: Firewood Shortagementioning
confidence: 99%
“…The overuse of fuelwood is significantly sharing the deforestation process. In addition to this, there was increased use of crop residues and cow dung as fuel which was depriving the agricultural soil of valuable nutrients and organic matter resulting to reduce the productive capacity of land [14].…”
Section: Types Sources and Quantity Of Biomass Consumptionmentioning
confidence: 99%